Fundraising skills for health care executives - Fitzpatrick, Joyce J., 1944- (Springer Pub., 2000)
No one prepares the new dean or health care executive for the fundraising aspect of their profession. Rather, it is one of the skills that is expected but not explicitly taught. Here, a former Dean and a Director of Major Gifts for a renowned nursing institution, with a combined 50 years in the profession, present an explicit, hands-on guide to successful fundraising among individuals, foundations, and corporations. From the basic principles of development to the specifics of tax regulations and the sometimes delicate matter of stewardship, this book articulates strategies for success. Case st.